Spectroscopic and antibacterial studies of new octaazamacrocyclic complexes derived from carbohydrazide and isatin - Kumar, Krishan; Kamboj, Monika; Jain, Kiran; Singh, D. P. (Spectrochimica Acta Part A-Molecular and Biomolecular Spectroscopy, 2014)
A novel series of the macrocyclic complexes of the type: [M(C18H14N10O2)X-2], where M = Co(II), Ni(II), Cu(II) and Zn(II); X = Cl-, NO3- and CH3COO-, has been synthesized by template condensation of carbohydrazide and isatin in methanolic medium. The complexes were characterized by various physico-chemical techniques, such as elemental analyses, molar conductance measurements, magnetic measurements, and electronic, NMR, IR and EPR spectral studies. The low value of molar conductance indicates them to be non-electrolytes. Based on various studies, a distorted octahedral geometry was proposed for all the metal complexes. Metal complexes were tested for their in vitro antibacterial activities against some pathogenic bacterial strains and compared with standard antibiotic, Ciprofloxacin. Some of the tested complexes was found effective against Gram-positive bacterial strains. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Carbohydrazide; Isatin; Macrocyclic complexes; MIC; Template condensation

Efficient route to 3,3 `-biindolinylidene-diones by iron-catalyzed dimerization of isatins - Jagtap, Rahul A.; Pradhan, Chandini; Gonnade, Rajesh G.; Punji, Benudhar (Chemistry-an Asian Journal, 2022)
Iron-catalyzed dimerization of various isatin derivatives is described for the efficient synthesis of 3,3 `-biindolinylidene-diones (isoindigos). The reaction provides easy access to self-coupled and cross-coupled 3,3 `-indolinylidene-diones that have high relevance to biology and materials. This Fe(0)- or Fe(II)-catalyzed dimerization reaction tolerates a wide range of functionalities, such as fluoro, chloro, bromo, alkenyl, nitrile, ether, ester, pyrrolyl, indolyl and carbazolyl groups, including cyclic and acyclic alkyls as well as an alkyl-bearing fatty-alcohol moiety. Especially, the coupling between two distinct isatins provided excellent selectivity for the cross-dimerization with trace of self-couplings. The single-crystal X-ray diffraction study established the molecular structure of eight dimerized products. A preliminary mechanistic study of the Fe-catalyzed dimerization supported the radical pathway for the reaction.
Keywords: Cross-coupling; dimerization; iron; Isatin; Isoindigo; Mechanism

Iron-catalyzed C-C and C-N bond-forming tandem amidation offering access to 3-amino-3-aminomethyl-2-oxindole frameworks - Ankade, Shidheshwar B.; Pradhan, Chandini; Samal, Pragnya Paramita; Gonnade, Rajesh G.; Krishnamurty, Sailaja; Punji, Benudhar (Advanced Synthesis & Catalysis, 2024)
An iron-catalyzed protocol for the synthesis of 3-amino-3-aminomethyl-2-oxindole heterocyclic structures is disclosed employing isatins and non-nucleophilic N-methoxybenzamides. This reaction class is associated with broad scope and tolerates numerous functionalities, such as fluoro, chloro, bromo, iodo, trifluoromethyl, nitrile, ester, ether, and alkenyl, including heteroaryl - thiophene, benzothiophene, carbazolyl, indolyl, eugenol, and polycyclic cholesterol moieties. Detailed mechanistic investigations reveal that the reaction proceeds via iron-catalyzed N-O bond cleavage in N-methoxybenzamides, generating formaldehyde and benzamide, and through the intermediacy of isatin-ketimines and N-(hydroxymethyl)benzamides. Overall, this amidation reaction involves one C-C and two C-N bond-forming tandem processes, providing a range of beta-amino-aminomethyl-oxindoles (45 examples) in up to 88% yields. image
Keywords: benzamide; iron; Isatin; tandem amidation; tetrasubstituted carbon stereocenter